Kepribadian Dependent Pada Mahasiswa Universitas Malikussaleh - Rahilati Izka (Jurnal Psikologi Terapan, 2018)
Each human born with different personality characteristic. When everone is born with the same personality traits, then we do not need other people, because they consider themselves perfect. But not to dependent on other. The creation of a adependen personality measuring instrument is expected to help investigate examinations or interventions related to personality dependen on a study. The subject of research is 60 people that all of them consist of students University Malikussaleh 10% student semester 1, 30% student semester 3, 60% student semester 5, based on psychometric tests conduced through internal consistency and construct valisity test. The scale of personality dependent on having high validity and reliability. This scale can measure on consistent construction consistently, can distinguish individuals belonging to high or low dependent personality traits. The dimensions of the dependent personality are incable of making decisions and sensitive to small things. With very good psychometric standards, this scale can be used in a variety of local studies to measure dependent personality.